Meningkatan Hasil Belajar PAI Menggunakan Model Pembelajaran PBL di Kelas V SDN 01 Kampung Parit Silayang - Resmita, Resmita (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in the Islamic Religious Education (PAI) subject with the topic Closer to Allah through Asmaul Husna in Grade V at SD Negeri 01 Kampung Parit Silayang by applying the Make a Match teaching method. The background of this research is the low level of students' understanding of PAI materials, lack of active student participation during lessons, and the dominance of lecture methods that make learning monotonous. The research method used is Classroom Action Research (CAR), which consists of several cycles, with each cycle involving planning, implementation, observation, and reflection stages. The research subjects were 8 Grade V students, consisting of 3 male students and 5 female students. Data were collected through observations, interviews, and learning outcome tests. The results indicate that the application of the Make a Match method effectively increased students' active participation in learning and their learning outcomes. The learning process became more engaging, enjoyable, and directly involved the students. The percentage of learning mastery increased from 62.5% at the beginning of the study to higher levels after the method was applied. Thus, the Make a Match method proved effective in enhancing the quality of PAI learning and improving students' learning outcomes.